Electrical Conductivity Distribution in Detonating Benzotrifuroxane - Satonkina, Nataliya (Sci Rep, 2018)
Electrical conductivity profile behind the detonation front in the benzotrifuroxane (BTF) was measured using high-resolution technique. BTF is a peculiar high explosive which is completely hydrogen-free: its molecular formula is C(6)N(6)O(6). Results are compared with the conductivity distributions in detonating hexogen (RDX, C(3)H(6)N(6)O(6)) and triaminotrinitrobenzene based explosive (TATB, C(6)H(6)N(6)O(6)). The conductivity in BTF was found to be similar to that observed in the common explosives which contain hydrogen. Thus, the contribution of hydrogen (e.g., ions produced by the dissociation of water) in the conductivity is minor, both in the reaction zone and in the final detonation products. The characteristics of the conductivity profiles generally support the idea of contact conductivity through the connected structures of carbon particles formed in the detonation wave.